Correction: Nanoparticle binding attenuates the pathobiology of gastric cancer-associated Helicobacter pylori. Issue 3 (8th January 2020) - Westmeier, Dana; Posselt, Gernot; Hahlbrock, Angelina; Bartfeld, Sina; Vallet, Cecilia; Abfalter, Carmen; Docter, Dominic; Knauer, Shirley K.; Wessler, Silja; Stauber, Roland H.
Abstract : Correction for 'Nanoparticle binding attenuates the pathobiology of gastric cancer-associated Helicobacter pylori ' by Dana Westmeier et al., Nanoscale, 2018, 10, 1453–1463.